KETERKAITAN SEKTOR PERTANIAN DALAM PEREKONOMIAN PROVINSI KALIMANTAN SELATAN (ANALISIS INPUT-OUTPUT) - Sari, Sarita Indah; Lada, Tri Hadi Sumitra; Taek, Egidius; Lili, Lili (Fakultas Pertanian, Universitas Janabadra, 2024)
South Kalimantan is one of the provinces with large plantation areas with a gross domestic product growth rate of 3.48% - 5.11% during 2023. This data shows that the rate of economic growth is still unstable, especially in the agricultural sector. This research aims to analyze the relationship between the agricultural sector and other sectors and key sectors in the economy of South Kalimantan Province. The data used is the input-output table published by the South Kalimantan Central Statistics Agency in 2016 for producer prices (millions of rupiah) with a classification of 52 sectors and aggregated into 27 sectors. The data analyzed are forward linkages, backward linkages and multiplier numbers. The research results show that the highest backward linkage value is in the food crop sector at 1.518. This means that this sector still needs a lot of raw materials from other sectors to develop. The highest value of future linkage is the agricultural and hunting services sector, this sector acts as a provider of raw materials for the growth of other sectors. The agricultural sectors that support this region are agricultural and hunting services, food crop farming, animal husbandry, fisheries, seasonal and annual plantations and seasonal horticultural crop farming, annual horticulture, and others. However, the multiplier effect on output, income and the number of workers in the agricultural sector is still lower than in other sectors. Therefore, the growth of the agricultural sector is closely related to other sectors. Key words: Agricultural sector linkages, GRDP, Iput-Output analysis, South KalimantanINTISARI Kalimantan Selatan salah satu Provinsi dengan areal perkebunan yang luas dengan tingkat pertumbuhan produk domestik bruto sebesar 3,48%-5,11% selama tahun 2023. Data ini menunjukkan masih belum stabilnya laju pertumbuhan ekonomi terutama pada sektor pertanian. Penelitian ini bertujuan untuk menganalisis keterkaitan sektor pertanian dengan sektor lain dan sektor kunci dalam perekonomian Provinsi Kalimantan Selatan. Data yang digunakan yaitu tabel input-output yang diterbitkan Badan Pusat Statistik Kalimantan Selatan tahun 2016 untuk harga produsen (jutaan rupiah) dengan klasifikasi 52 sektor dan diagregasikan menjadi 27 sektor. Data yang dianalisis yaitu keterkaitan ke depan, keterkaitan ke belakang dan angka pengganda. Hasil penelitian menunjukkan nilai keterkaitan ke belakang tertinggi adalah sektor tanaman pangan sebesar 1,518 artinya, sektor tersebut masih membutuhkan banyak bahan baku dari sektor lain untuk berkembang. Nilai tertinggi dari keterkiatan ke depan adalah sektor jasa pertanian dan perburuan, sektor ini berperan sebagai penyedia bahan baku untuk pertumbuhan sektor lainnya. Sektor pertanian yang mendukung diwilayah ini adalah jasa pertanian dan perburuan, pertanian tanaman pangan, peternakan, perikanan, perkebunan semusim dan tahunan dan pertanian tanaman hortikultura semusim, hortikultura tahunan, dan lainnya. Namun, multiplier effect terhadap output, pendapatan, dan jumlah tenaga kerja dari sektor pertanian masih lebih rendah dibandingkan dengan sektor lainnya. Oleh karena itu pertumbuhan sektor pertanian sangat berkaitan dengan sektor-sektor lainnya. Kata kunci: Keterkaitan sektor pertanian, PDRB, analisis Iput-Output, Kalimantan Selatan